Internationalization to what purposes?: Marketing to international students - Gary Rhoades (Laureate Education Inc, 2016)
Amidst global discourse about universities' internationalization, how do universities position themselves and their purposes in recruiting international students?  For professionals working to establish partnerships and increase cultural enrichment both on their home campuses and through international exchange, the purposes that are often foregrounded in professional associations speak to the public good, to the broad social benefits of such activities.  However, my research on the marketing that international offices at four universities in the UK and U.S. are doing to international students suggest that as in the marketing of U.S. universities to domestic students, it is the private benefits of higher education, to the students and to the individual institutions that are predominant (Hartley and Morphew, 2008; Saichaie and Morphew, 2014).